The integration paradox: Does awareness of the extent of ethno-racial discrimination increase reports of discrimination? - Merlin Schaeffer; Judith Kas (Political Psychology, 2024)
The “integration paradox” posits that seemingly well-established immigrants and their descendants tend to report more discrimination compared to their more marginalized peers. This study investigates one potential mechanism for this paradox, namely, the increasing awareness of their group's enduring ethno-racial minority status. Through a survey experiment with approximately 1000 randomly sampled immigrants and their descendants in Germany, this study provides the first causal evidence for this awareness mechanism. Participants were randomly assigned to read either a news article highlighting ethno-racial hiring discrimination in the German labor market or an unrelated news article on astrophysics. Our findings demonstrate that exposure to the discrimination-related article elicits a significant increase in reports of discrimination experienced by members of the groups with whom minorities identify, but also in self-reported personal experiences of discrimination. This suggests that increased awareness can alter how minorities frame their personal experiences or encourage them to disclose instances of discrimination that they would have previously kept private. The study further reveals that heightened awareness does not translate into a corresponding increase in political demands for improved antidiscrimination policy. Finally, a third experimental condition dispels concerns that news reports downplaying ethno-racial labor market penalties could stifle minorities' propensity to report discrimination experiences.
Keywords: 320